Natividade e o recenseamento de sua população (1872 – 1920) - Menezes, Ivaldino Ferreira de (2023)
This dissertation aims to present the population aspects of the population of the municipality of Natividade, based mainly on the censuses carried out in Brazil in the years 1872 and 1920. At first, a chronological description of the history of the occupation of Goiás is presented, with emphasis on the settlement of Natividade, an important city in the north of that state. In the second moment, the work emphasizes the population of Natividade observing origin, sex, race, religion, schooling and the professions performed by the census residents, with the purpose of understanding the social dynamics that characterized the occupation of the region. Through the demographic census that supports the research, it was also observed the land situation of Natividade.